Services according to mental health needs for youth in foster care? - A multi-informant study - Marit Larsen; Valborg Baste; Ragnhild Bjørknes; Trine Myrvold; Stine Lehmann (BMC, 2018)
Abstract Background Foster children have a high risk of mental disorders. This has contributed to increased international attention to service utilization for youth in foster care. The aim of this study is to examine whether youth in foster care receive services according to need, by using a multi-informant design. Method Detailed information on the type and frequency of service use during the last 2 years and on youth mental health were collected from foster youths and their carers in Norway (n = 405, aged 11-17 years) through online questionnaires. Mental health was assessed with the Strengths and Difficulties Questionnaire. Statistical analyses were conducted using descriptive statistics and log-binominal regressions. Results In total, 48.8% of foster youths showed evidence of mental health problems, and 74.5% of foster families had contact with services. Increased mental health problems and living in non-kin foster care were associated with more service use. Youths with mental health problems had twice the probability of receiving services from the child and adolescent mental health service (CAMHS) and primary health care services compared to youths without problems. However, 57.0% of youths with carer-reported mental health problems did not have contact with CAMHS. Conclusions Service use among foster youths was associated with service need rather than demographic and placement characteristics. The majority of youths with mental health problems did not receive services from CAMHS. However, many of them were in contact with primary health care services.